2015
DOI: 10.1149/2.0131508jss
|View full text |Cite
|
Sign up to set email alerts
|

Structural Analyses of Thin SiO2Films Formed by Thermal Oxidation of Atomically Flat Si Surface by Using Synchrotron Radiation X-Ray Characterization

Abstract: Partially crystalline structures in thin SiO 2 films formed by thermal oxidation of atomically flat Si surface were investigated by performing X-ray reflectometry and grazing incidence X-ray diffraction measurements. The densities of the SiO 2 films were higher than those of amorphous SiO 2 films, especially at the SiO 2 /Si interface. The structure of thermally grown SiO 2 has been expected to be amorphous, but sharp diffraction peaks were observed in GIXRD measurements. The diffraction peaks tended to reflec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In contrast, several studies were reported that certain thermally grown SiO2 films consist of crystalline domains [16,17], so the polycrystalline SiO2 phase can be plausibly expected along with the amorphous phase in the annealed films. Nagta et al reported that the thermally grown crystalline SiO2 by means of thermal oxidation possess high density which is about 4.4 g/cm 3 , while the amorphous phase density was about 2.2 g/cm 3 [18]. The cross-sectional TEM image of the Si/sapphire film oxidized at 823 K is presented in Figure 1b.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, several studies were reported that certain thermally grown SiO2 films consist of crystalline domains [16,17], so the polycrystalline SiO2 phase can be plausibly expected along with the amorphous phase in the annealed films. Nagta et al reported that the thermally grown crystalline SiO2 by means of thermal oxidation possess high density which is about 4.4 g/cm 3 , while the amorphous phase density was about 2.2 g/cm 3 [18]. The cross-sectional TEM image of the Si/sapphire film oxidized at 823 K is presented in Figure 1b.…”
Section: Methodsmentioning
confidence: 99%